Self-efficacy, symptoms and physical activity in patients with an anterior cruciate ligament injury: a prospective study - Thomeé, P.; Währborg, P.; Börjesson, M.; Thomeé, R.; Eriksson, B. I.; Karlsson, J. (Scandinavian journal of medicine & science in sports, 2007)
Self‐efficacy belief may be of major importance for the outcome of rehabilitation after sports‐related injuries. A new instrument, the Knee Self‐Efficacy Scale (K‐SES), was used to evaluate the role of perceived self‐efficacy in patients with an anterior cruciate ligament (ACL) injury. The purpose of this prospective exploratory study was to describe the patients' perceived self‐efficacy at various times post‐injury and surgery, respectively, for responsiveness of the K‐SES and to correlate the K‐SES score with the patients' subjective symptoms. The purpose was also to describe the influence of gender, age and physical activity on the patients' perceived self‐efficacy. Thirty recently injured patients with an ACL‐deficient knee and 33 patients who had undergone ACL reconstruction reported their physical activity level and their perceived self‐efficacy on four test occasions during a 1‐year period. The patients' subjective knee symptoms were documented on two of the test occasions. A significant increase in the K‐SES score was seen after injury as well as after surgery, during the course of rehabilitation. Pre‐operatively, men's perceived self‐efficacy was significantly (P=0.013) higher compared with women's self‐efficacy. Patients with a high baseline (pre‐injury) physical activity level (Tegner 7–10) perceived their self‐efficacy as being significantly (P=0.005) higher pre‐operatively compared with patients with a low baseline activity level (Tegner 3–6). “Younger” (age 17–29), recently injured patients, perceived their self‐efficacy as being significantly (P=0.034) higher compared with “older” patients (age 30–54). At the 12‐month test, 15 of 30 patients with an ACL‐deficient knee and 15 of 33 patients who had undergone ACL reconstruction reported that they had returned or nearly returned to their baseline physical activity level. The subjective knee outcome score, as measured by the Knee Injury and Osteoarthritis Outcome Score (KOOS), improved significantly (P<0.01) during rehabilitation, apart from the KOOS subscale of “pain” (P=0.077) for patients who had undergone ACL reconstruction. There was a “low” to “strong” correlation (rs=0.0–0.7) between the K‐SES and the five subscales in the KOOS. We conclude from the present study that K‐SES has good responsiveness with significantly increased self‐efficacy during the rehabilitation process for patients with an ACL‐deficient knee as well as for patients who had undergone ACL reconstruction. The improvement in perceived self‐efficacy could, however, only be partly explained by the improvement in subjective symptoms. Furthermore, self‐efficacy differed significantly with gender, age and physical activity level early in the rehabilitation process.